Interação entre resíduo da matéria orgânica natural e metais potencialmente tóxicos - Jacundino, Jonas Soares (Universidade Federal de São Carlos, 2021)
The contribution of potentially toxic metals in aquatic systems, whether of natural or anthropogenic origin, is an issue that has been worrying the Scientific Community over the years. This is mainly due to the wide applicability and toxicity of these species, in addition to not being chemically or biologically degraded, cycling through the environment. Substances capable of interacting with these metals, influencing their input, transport and (bio)availability are of great environmental interest. Among the main natural organic complexing agents present in natural ecosystems, humic substances (HS) stand out. The HS have an operational definition and can be obtained by alkaline extraction, for example, from matrices such as soils and sediments. After the extraction process, a poorly soluble fraction is also generated, which is often discarded, and the soluble fractions of HS called humic and fulvic acids are widely used. Thus, showing an applicability for this poorly soluble material is of economic, social and environmental interest, since it reduces the amount of waste generated without specific applicability. This poorly soluble fraction, called in this work as Residue Of Natural Organic Matter (RO-NOM) has promising characteristics to function as a chelating resin for organic and inorganic species, including potentially toxic metals (PTM). Thus, in this work, the characterization of RMON obtained after alkaline extraction from different soils collected in different regions through the techniques of Visible Ultraviolet (UV-VIS), Infrared Spectroscopy (IR) and Nuclear Resonance Magnetic (NMR), and interaction of these residues with potentially toxic metals (copper and chromium) at different pH was also evaluated, aiming at its application as a chelating resin for remediation of contaminated matrices. A tangential ultrafiltration system was used to verify the interaction between RO-NOM and PTM. The results obtained indicated that the RO-NOM has distinct characteristics, and the RO-NOM extracted from State of São Paulo has higher organic matter content and greater retention of the evaluated PTM. The pH 6 indicated the highest retention of copper and chromium PTM. With the very satisfactory results obtained, the promising potential of the applicability of RO-NOM in natural systems can be evidenced.
Interaction between natural organic matter residue and potentially toxic metals
Keywords: Resíduo da matéria orgânica natural; Caracterização; Metais potencialmente tóxicos.; Residue of natural organic matter; Characterization; Potentially toxic metals; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL